Selection of tolerant species for contaminated soil phytemedication using imazapic - Vasconcelo, Simonny Montthiel Araújo; Jakelaitis, Adriano; Costa, Mailon Lucas Meurer; Oliveira, Romário Rodrigues Cunha de; Santos, Vanessa Silva (Revista de Ciências Agroveterinárias, 2020)
Imazapic can cause visual intoxication in sensitive crops sown in rotation given its long residual effect in the soil and represents ecotoxicological risks in aquatic environments. In this scenario, phytoremediation is an innovative proposal as an alternative method for removing organic pollutants, with its success depending on the careful selection of plants with favorable characteristics. The objective of this study was to identify imazapic-tolerant plant species for potential use in phytoremediation programs. Eight experiments were conducted in a greenhouse using the species Panicum maximum, Crotalaria juncea, Stylosanthes spp., Cajanus cajan, Dolichos lablab, Pennisetum glaucum, Mucuna aterrima, and Raphanus sativus, considering five doses of imazapic (0; 58.33; 87.5; 175 and 350 g ha-1). The treatments were delineated in randomized blocks with four replicates. The symptoms of visual toxicity, height, and dry mass of the plants were determined at 30 and 60 days after plant emergence and at the end of the experiment. The species M. aterrima, C. cajan, and D. lablab presented no visual symptoms of phyto-intoxication. M. aterrima promoted greater dry mass production when cultivated as a control, and exposure to imazapic did not affect this characteristic. Height and dry mass reduction required higher doses in tolerant species, although the results were not significant for D. lablab and C. cajan. Among the studied species, M. aterrima stood out for its high biomass production, promising phytoremediation of sites with imazapic residues.